Study of communication phenomenology of Tiktok users who have experienced fear of missing out on behavior - Wirman, Welly; Yozani, Ringgo Eldapi; Angela, Sesdia; Surbakti, Rian Stevanus (Bricolage : Jurnal Magister Ilmu Komunikasi, 2023)
TikTok users who experience fear of missing out behavior is a new phenomenon in the development of TikTok social media. This study aims to know the meaning of TikTok social media for TikTok users who experience Fear of Missing Out behavior. This study uses a qualitative research method with a phenomenological approach and uses qualitative research data analysis techniques according to the analysis of the Miles & Hubermen model. The results show that the utilization and use of TikTok for TikTok users who experience fear of missing out behavior are influenced by 2 motives, firstly, past motives (because motives) which are classified as sociogenetic motives, in the form of curiosity motives, documentation motives and future motives (in order). To motive which are classified as sociogenetic motives, namely curiosity motives, self-esteem motives, and competence motives, there are also biological motives, namely eliminating boredom as well as improving the mood where a person needs rest activities. Meanwhile, the meaning of TikTok for TikTok users who experience fear of missing out behavior is as a medium of information, as a versatile and functional medium, and as a space for creativity.